2012
DOI: 10.1124/mol.112.078642
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Reduced Folate Carrier-Mediated Folate/Antifolate Transport through an Antiport Mechanism with 5-Aminoimidazole-4-Carboxamide Riboside Monophosphate

Abstract: 5-Aminoimidazole-4-carboxamide riboside (AICAR), an agent with diverse pharmacological properties, augments transport of folates and antifolates. This report further characterizes this phenomenon and defines the mechanism by which it occurs. Exposure of HeLa cells to AICAR resulted in augmentation of methotrexate, 5-formyltetrahydrofolate, and 5-methyltetrahydrofolate initial rates and net uptake in cells that express the reduced folate carrier (RFC). This did not occur in cells that express only the proton-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In support of this model are reports that MTX transport is competitively inhibited by structurally diverse organic anions such as adenine nucleotides and thiamine phosphates (Goldman, 1971). Further, thiamine pyrophosphate and ZMP (AICA ribonucleotide) are bona fide RFC substrates which, when present within cells, trans-stimulate folate influx by RFC while inhibiting (anti) folate export via this mechanism (Zhao et al, 2001b(Zhao et al, , 2002Visentin et al, 2012b). Although RFC generates only small transmembrane chemical gradients, when considered in light of the dianionic nature of folates and membrane potentials, RFC generates substantial electrochemical potentials across the plasma membrane (Goldman et al, 1968;Goldman, 1971).…”
Section: Biology Of Rfcmentioning
confidence: 67%
See 1 more Smart Citation
“…In support of this model are reports that MTX transport is competitively inhibited by structurally diverse organic anions such as adenine nucleotides and thiamine phosphates (Goldman, 1971). Further, thiamine pyrophosphate and ZMP (AICA ribonucleotide) are bona fide RFC substrates which, when present within cells, trans-stimulate folate influx by RFC while inhibiting (anti) folate export via this mechanism (Zhao et al, 2001b(Zhao et al, , 2002Visentin et al, 2012b). Although RFC generates only small transmembrane chemical gradients, when considered in light of the dianionic nature of folates and membrane potentials, RFC generates substantial electrochemical potentials across the plasma membrane (Goldman et al, 1968;Goldman, 1971).…”
Section: Biology Of Rfcmentioning
confidence: 67%
“…The original finding that AICA ribonucleoside regulates hRFC transport (McGuire et al, 2006) now appears to be unrelated to the activating effect of AICA ribonucleotide (ZMP) on AMP-activated protein kinase (AMPK), but rather reflects trans-stimulation of hRFC by intracellular ZMP (Visentin et al, 2012b) (described previously).…”
Section: Biology Of Rfcmentioning
confidence: 99%
“…R1-11-RFC-6 and R1-11-PCFT-4 are stable transfectants of R1-11 cells that express RFC and PCFT, respectively, at a level similar to that of HeLa cells (Zhao et al, 2008). R1-11-PCFT-h is a stable transfectant of R1-11 cells with levels of PCFT expression much higher than that of HeLa cells (Visentin et al, 2012). Cells were grown in RPMI medium supplemented with 10% fetal bovine serum, 100 units/ml penicillin, and 100 mg/ml streptomycin.…”
Section: Introductionmentioning
confidence: 99%
“…Visentin et al have reported that pretreatment of HeLa cells with AICA riboside results in augmentation of MTX initial rates and net uptake in cells [36] . There may be an interaction between MTX and AICA riboside, and further studies on the influence of AICA riboside on the antitumor efficacy and pharmacokinetics of MTX are needed.…”
Section: Discussionmentioning
confidence: 99%